Risk Biomarkers for Biochemical Recurrence after Radical Prostatectomy for Prostate Cancer Using Clinical and MRI-Derived Semantic Features - Guerra, Adalgisa (2023)
Funding Information: This work is supported by a PhD student scholarship (A.G.) from the Luz Saúde Clinical Research and Innovation program, Award Number: ID LH.INV.F2019027. This work is also partially financed by national funds through FCT—Fundação para a Ciência e Tecnologia, Portugal, under the project UIDB/00006/2020. Publisher Copyright: © 2023 by the authors.